2018
DOI: 10.1089/apc.2018.0114
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Stigma by Healthcare Providers in the United States: A Systematic Review

Abstract: Reducing HIV-related stigma may enhance the quality of HIV prevention and care services and is a national prevention goal. The objective of this systematic review was to identify studies of HIV-related stigma among healthcare providers. For studies published between 2010 and 2017, we: (1) searched databases using our keywords, (2) excluded nonpeer reviewed studies, (3) limited the findings to the provider perspective and studies conducted in the United States, (4) extracted and summarized the data, and (5) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
141
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 180 publications
(156 citation statements)
references
References 15 publications
11
141
0
4
Order By: Relevance
“…Educational intervention had a signi cant effect on improving HIV/AIDS knowledge, changing HIV attitudes and reducing the proportion of workers with extra-partners, and could also change premarital and paid sexual behavior when combined with community intervention. A recent systematic review showed that educational intervention combined with community intervention could also change the public stigma of HIV [51]. In the future, more attention should be paid to HIV education combined with community intervention [52].…”
Section: Discussionmentioning
confidence: 99%
“…Educational intervention had a signi cant effect on improving HIV/AIDS knowledge, changing HIV attitudes and reducing the proportion of workers with extra-partners, and could also change premarital and paid sexual behavior when combined with community intervention. A recent systematic review showed that educational intervention combined with community intervention could also change the public stigma of HIV [51]. In the future, more attention should be paid to HIV education combined with community intervention [52].…”
Section: Discussionmentioning
confidence: 99%
“…They are also uniquely situated to educate patients on the risks and benefits of PrEP and have the ability to reach a large number of high-risk individuals. Two prior reviews have highlighted the substantial breadth of research on barriers to PrEP use among populations with higher rates of HIV, 19,20 and two other reviews have incorporated health care provider barriers to PrEP service delivery, 21,22 but a comprehensive and systematic review on provider-level barriers to PrEP prescription was needed.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-related stigma exhibited by health care workers in the South is prevalent, and provider characteristics such as race, religion, and clinic type may predict stigmatizing attitudes. [26][27][28] Research has also shown that personal values held by providers may interfere with discussing sexual behaviors with their patients, 25 and patient anticipated stigma in health care settings has been correlated with lower adherence to ART. 29 This underscores that targeted educational and stigma reduction efforts with providers in the southern United States, like those who participated in this study, are warranted.…”
Section: Geographic Information System Results/analysismentioning
confidence: 99%